ANALISI FAKTOR YANG BERHUBUNGAN DENGAN PENERIMAAN IBU TERHADAP IMUNISASI MR PADA MURID SEKOLAH DASAR - Erni Aisyah Hasibuan; Megawati Sinambela (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
The promotion of Measles Rubella immunization campaign is a government strategy to achieve elimination of measles and rubella by 2020. This immunization is targeting all Indonesian children between the ages of nine months and 15 years and will aim to reach 95% immunization coverage. Not all parents receive the MR immunization program. Air Merah Village is one of the villages that reject high immunization. This study is aimed to analyze the factors associated with mother’s acception of measles rubella immunization at primary school children of 112245 primary school at Air Merah Village, Kampung Rakyat Sub-district, South Labuhanbatu Districts. This study is a quantitative study with descriptive analytics method. This study uses Consecutive sampling techniques and the data are collected using questionnare with interview method. Data analysis procedure of this study used univariat, bivariat and multivariat with chi-square test. The result shows that 73,3% respondents did not received measles rubella immunization. The result of chi-square test show that variabel education level, job status, knowledge about measles rubella immunization, perceived susceptibility, perceived severity, perceived benefit, perceived barriers, and family supports are significantly associated with the acceptance of measles rubella immunization (p-value < 0,05). While age variableare not significantly associated with acceptance of measles rubella immunization (v-value > 0,05). Sugestion from this study, it needs to give more education about the importance of measles rubella immunization from related parties to the parents, especially for mother, to improve their awareness to join measles immunization